Prediction of Monochorionic Diamniotic Twin Pregnancy Outcomes Based on Early Second Trimester Ultrasound - Slavica Aksam; Jelena Dotlic; Dusica Kocijancic Belovic; Mirjana Marjanovic Cvjeticanin; Ivana Vukovic; Milena Mitrovic; Ivana Babovic; Srboljub Milicevic; Snezana Plesinac; Snezana Buzadzic (IMR Press, 2023)
Background: Association between second trimester ultrasound findings and twin pregnancy outcome is still unclear. Study aimed to evaluate the performance of second trimester ultrasound scan in the prediction of monochorionic diamniotic twin pregnancies outcomes. Methods: Prospective-cohort study of all consecutive healthy women with monochorionic twin pregnancies followed-up and delivered in five years was undertaken. During second trimester screening (16-18 weeks) fetal biometry was measured (biparietal diameter-BPD, abdominal circumference-AC, femur length-FL, estimated fetal weight-EFW) and inter-twin discordance noted. Amniotic fluid amount was determined. Pregnancy outcomes were having live-born twins, Apgar sores and birth-weights, pregnancy complications and gestational week of delivery. Results: Receiver operating characteristics (ROC) analysis showed that BPD (p = 0.018), AC (p = 0.019) and FL (p = 0.015) were good predictors of having live-born twins. Regression analysis showed that the most important factors influencing twins' survival to term were inter-twin AC, BPD and FL differences. Fetal discordance in BPD, AC and FL explained correctly 76.3%, 76.5% and 58% of pregnancy outcomes. If second trimester inter-twin BPD difference was <2.5 mm, AC difference was <17 mm and FL difference was <1.5 mm survival of twins was better, complications were less frequent, delivery mostly occurred closer to term, twins had higher birth-weights and better Apgar scores. Second trimester EFW of twin and its difference as well as the amniotic fluid amount were not associated with examined pregnancy outcomes. Conclusions: Discordant twins' growth in the second trimester registered by ultrasound reliably implies on adverse monochorionic diamniotic twin pregnancy outcome.